Postcranial Pneumaticity and Bone Structure in Two Clades of Neognath Birds. Issue 6 (1st April 2013) - Gutzwiller, Sarah C.; Su, Anne; O'Connor, Patrick M.
ABSTRACT Most living birds exhibit some degree of postcranial skeletal pneumaticity, aeration of the postcranial skeleton by pulmonary air sacs and/or directly from the lungs. The extent of pneumaticity varies greatly, ranging from taxa that are completely apneumatic to those with air filling most of the postcranial skeleton. This study examined the influence of skeletal pneumatization on bone structural parameters in a sample of two size‐ and foraging‐style diverse (e.g., subsurface diving vs. soaring specialists) clades of neognath birds (charadriiforms and pelecaniforms). Cortical bone thickness and trabecular bone volume fraction were assessed in one cervical and one thoracic vertebra in each of three pelecaniform and four charadriiform species. Results for pelecaniforms indicate that specialized subsurface dive foragers (e.g., the apneumatic anhinga) have thicker cortical bone and a higher trabecular bone volume fraction than their non‐diving clademates. Conversely, the large‐bodied, extremely pneumatic brown pelican (Pelecanus occidentalis) exhibits thinner cortical bone and a lower trabecular bone volume fraction. Such patterns in bone structural parameters are here interpreted to pertain to decreased buoyancy in birds specialized in subsurface dive foraging and decreased skeletal density (at the whole bone level) in birds of larger body size. The potential to differentially pneumatize the postcranial skeleton and alter bone structure may have played a role in relaxing constraints on body size evolution and/or habitat exploitation during the course of avian evolution. Notably, similar patterns were not observed within the equally diverse charadriiforms, suggesting that the relationship between pneumaticity and bone structure is variable among different clades of neognath birds. Anat Rec, 296:867–876, 2013. © 2013 Wiley Periodicals, Inc.